Annotating and prioritizing genomic variants using the Ensembl Variant Effect Predictor—A tutorial. Issue 8 (2nd December 2021) - Hunt, Sarah E.; Moore, Benjamin; Amode, Ridwan M.; Armean, Irina M.; Lemos, Diana; Mushtaq, Aleena; Parton, Andrew; Schuilenburg, Helen; Szpak, Michał; Thormann, Anja; Perry, Emily; Trevanion, Stephen J.; et al.
Abstract: The Ensembl Variant Effect Predictor (VEP) is a freely available, open‐source tool for the annotation and filtering of genomic variants. It predicts variant molecular consequences using the Ensembl/GENCODE or RefSeq gene sets. It also reports phenotype associations from databases such as ClinVar, allele frequencies from studies including gnomAD, and predictions of deleteriousness from tools such as Sorting Intolerant From Tolerant and Combined Annotation Dependent Depletion. Ensembl VEP includes filtering options to customize variant prioritization. It is well supported and updated roughly quarterly to incorporate the latest gene, variant, and phenotype association information. Ensembl VEP analysis can be performed using a highly configurable, extensible command‐line tool, a Representational State Transfer application programming interface, and a user‐friendly web interface. These access methods are designed to suit different levels of bioinformatics experience and meet different needs in terms of data size, visualization, and flexibility. In this tutorial, we will describe performing variant annotation using the Ensembl VEP web tool, which enables sophisticated analysis through a simple interface. Abstract : The Ensembl Variant Effect Predictor (VEP) is a freely available, open‐source tool for the annotation and prioritization of genomic variants. It maps variants to functionally relevant genomic regions and predicts their consequence. In this tutorial, we explain how to use the Ensembl VEP web interface and describe the available annotation options, including reference population frequency data, phenotype associations, variant citation data, and pathogenicity predictors.